Perceived physical literacy instrument for adolescents: A further validation of PPLI - Sum, Raymond K.W. (J Exerc Sci Fit, 2018)
BACKGROUND/OBJECTIVE: The purpose of this study is to examine the reliability and validity of “Perceived Physical Literacy Instrument” (PPLI) questionnaire in adolescents. METHODS: Based on physical literacy literature, a 9-item instrument was developed for initial tests. The self-report measure was administered to 1945 adolescents in Hong Kong. Confirmatory factor analysis (CFA) was used to examine a three-factor structure of physical literacy. A chi-square difference test analysed several competing models and compared the results between the proposed models (i.e., a three-factor solution) and other alternative models (i.e., a one-factor or two-factor solution). Furthermore, the measurement invariance across gender groups was examined by using multiple-group confirmatory factor analysis. Mean scores for physical literacy factors were also examined by demographic characteristics. RESULTS: Confirmatory factor analysis (CFA) showed that the construct demonstrated a good fit to the model. For convergent validity, our results, evaluating the factor loading of each items, the values of composite reliability (CR) and the average variance extracted (AVE) of the three factors, revealed that the three-factor validity of physical literacy was satisfactory. The chi-square difference test between models was significant indicating that all the latent variables had satisfactory discriminant validity. Moreover, the findings of measurement invariance showed that the PPLI is invariant across gender. CONCLUSIONS: The PPLI thus appeared to be reliable and valid as a measure of the perceived physical literacy of adolescents. Thus, along with other validated instruments, protocols and research designs, the PPLI could be widely used to test adolescents' self-perception of physical literacy and their own physical and mental health conditions and thereby health. Physical education professionals may thus recommend appropriate intervention programmes for younger generations.